1999
DOI: 10.1111/j.1471-6402.1999.tb00380.x
|View full text |Cite
|
Sign up to set email alerts
|

Who Fills out A “Lesbian” Questionnaire?

Abstract: Most research on lesbians has used self‐report questionnaires, and assumed that respondents who complete a “lesbian” questionnaire self‐identify as lesbians and engage in sexual relationships with women. The present study examined the degree to which 2,393 women who answered a “Lesbian Wellness Survey” are distributed on five aspects of lesbian sexuality and the coming‐out process. The five aspects were: (a) Sexual Orientation (numerical rating of sexual identity from exclusively lesbian/gay to exclusively het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…Just as research with LGB samples has found only weak associations between the dimensions of sexual identity, sexual behavior, and sexual relationships (cf. Geary et al, 2018;Laumann et al, 1994;Morris & Rothblum, 1999), our findings demonstrate that asexual identity is not synonymous with lack of sexual attraction, sexual behavior, or an intimate relationship. Compared with non-asexual individuals, asexuals were less likely to report having had sex in the 5 years prior to the survey.…”
Section: Prevalence and Demographic Profile Of Asexual Individualssupporting
confidence: 44%
See 1 more Smart Citation
“…Just as research with LGB samples has found only weak associations between the dimensions of sexual identity, sexual behavior, and sexual relationships (cf. Geary et al, 2018;Laumann et al, 1994;Morris & Rothblum, 1999), our findings demonstrate that asexual identity is not synonymous with lack of sexual attraction, sexual behavior, or an intimate relationship. Compared with non-asexual individuals, asexuals were less likely to report having had sex in the 5 years prior to the survey.…”
Section: Prevalence and Demographic Profile Of Asexual Individualssupporting
confidence: 44%
“…This is a limitation because people who reported no sexual attraction or behavior may very well use heterosexual, LGB, or other identity terms. This is because there is no perfect overlap among sexual identity, sexual behavior, and sexual attraction (Geary et al, 2018;Laumann, Gagnon, Michael, & Michaels, 1994;Morris & Rothblum, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…However, other findings indic a t e d n o s i g n i f i c a n t e t h n i c / r a c i a l differences in attitudes toward homosexuality (Dube ´& Savin-Williams, 1999) or in fear of disclosing to others (Morris & Rothblum, 1999). In addition, although Black LGB individuals may disclose their sexual identity to fewer numbers of individuals (see above), they may be more likely than their White peers to disclose to someone at an earlier rather than a later age (Morris & Rothblum, 1999;Savin-Williams, 1998).…”
Section: Ethnic/racial Differences In Sexual Identity Formation and I...mentioning
confidence: 98%
“…However, there exists only partial support for this position in the available research. In studies of women (Morris & Rothblum, 1999) and male youths (Dubé & Savin-Williams, 1999), no racial/ethnic differences in sexual orientation (defined as erotic attractions for or fantasies about the same or other sex) or in sex of sexual partners were found. Yet, studies of sexual identity continually support significant racial/ethnic differences (e.g., Parks et al, 2004 …”
Section: Negotiated Identitiesmentioning
confidence: 92%